Listening to the Magnetosphere: How Best to Make ULF Waves Audible - Archer, Martin O.; Cottingham, Marek; Hartinger, Michael D.; Shi, Xueling; Coyle, Shane; Hill, Ethan “Duke”; Fox, Michael F. J.; Masongsong, Emmanuel V. (Frontiers in Astronomy and Space Sciences, 2022)
Observations across the heliosphere typically rely on in situ spacecraft observations producing time-series data. While often this data is analysed visually, it lends itself more naturally to our sense of sound. The simplest method of converting oscillatory data into audible sound is audification – a one-to-one mapping of data samples to audio samples – which has the benefit that no information is lost, thus is a true representation of the original data. However, audification can make some magnetospheric ULF waves observations pass by too quickly for someone to realistically be able to listen to effectively. For this reason, we detail various existing audio time scale modification techniques developed for music, applying these to ULF wave observations by spacecraft and exploring how they affect the properties of the resulting audio. Through a public dialogue we arrive at recommendations for ULF wave researchers on rendering these waves audible and discuss the scientific and educational possibilities of these new methods.